The Relationships Between First-Year Students' Sense of Purpose and Meaning in Life, Mental Health and Academic Performance (Journal of Student Affairs in Africa, 2021)
The research explored the relationships that exist between first-year students' sense of purpose and meaning in life, mental health and academic performance enrolled for courses with at-risk subjects at a higher education institution. Empirical data was obtained from 269 participants(18-22 years = 60.97%, female = 55.80%) who completed the Purpose in Life test and Mental Health Screening Questionnaire that assessed their sense of purpose and meaning in life and mental health. The average mark in four subjects during their mid-year examination denoted their academic performance. The results suggested that students were still exploring the nature of their sense of purpose and meaning in life (M = 109.21, SD = 21.05) and that small, significant relationships existed between their sense of purpose and meaning in life and mental health. These findings suggested that student practitioners should consider developing interventions to enhance first-year students' identification of their purpose and meaning in life that may inherently also aid their identity development. Likewise, practitioners should consider strengthening and/or developing interventions in critical mental health areas like depression, anxiety, post-traumatic stress and alcohol use behaviour.
Keywords: academic performance; first‑year student; Management Sciences; meaning in life; mental health; student development